3D unsteady turbulent flow analysis in a Francis turbine runner at nominal and off-design operating conditions - Loan, Pham Thi Kim; Ga, Bui Van (Vietnam Journal of Mechanics, 2004)
This paper presents the use of a commercial Navier-Stokes turbulent flow code (FLUENT) as a mean to evaluate the behavior of a Francis turbine runner for the design and off-design conditions. The flow in the runner is analyzed numerically at different operating points. The numerical results permit to observe physical phenomena in the runner that are important in the process of hydraulic turbo machinery design. Values of different velocity components in the flow, blade pressure distribution ... given by the model are compared with experimental data at nominal and off-design flow conditions. Computer resource involves in the flow analysis should be compatible with the need of design process of a runner. Therefore 12 hours of CPU time can be considered as acceptable for calculating at each operating point on a computer workstation of medium size power.